ISLAMIC MORTGAGE FINANCING: DETERMINATION OF AN OPTIMAL NISBAH OF PROFIT-SHARING SCHEME UNDER MUSHARAKAH MUTANAQISAH CONTRACT - Wulan Nurul Kamilah; Novriana Sumarti; Kuntjoro Adji Sidarto (PATTIMURA UNIVERSITY, 2026)
In an Islamic investment using a profit-sharing scheme, one of the important issues to be determined is the optimal value of nisbah, so that all the parties are fairly treated. This study aims to determine the optimal constant nisbah for an Islamic home financing under musharakah mutanaqisah (MMQ) contract, to ensure a fair arrangement for both parties: the Islamic Bank (IB) and the customer. Under MMQ, the model combines partnership (Musharakah) and a leasing agreement, with gradual ownership transfer from the IB to the customers using an installment payment. For describing its dynamic, the customer’s income is assumed to follow the Geometric Brownian Motion (GMB), and the defined objective function is solved using the simulated data of payments of rental fee and ownership installment. Based on the simulation results, it will show that the middle value of a parameter of the defined objective function as a biased portion, with , is not always chosen. The objective function, which shows a parabolic plot trend, can be interpreted as a fair situation between the IB and the customer. With the selected α value, the maximum objective function value will be sought. The determined nisbah can inform policy decisions in Islamic financial institutions.